Conditions of use of boom sprayers in the micro-region of Pato Branco, PR, Brazil - Modolo, Alcir José; Sgarbossa, Maicon; Pagnoncelli Junior, Fortunato de Bortoli; Brusamarello, Antônio Pedro; Dotto, Lucas; Freitas, Juan Paulo Xavier de; Baesso, Murilo Mesquita; Trogello, Emerson (Ciência e Natura, 2020)
The technical inspection of agricultural sprayers is responsible for generating important subsidies to inform and guide their users. In this sense, the aim of this study was to evaluate the working conditions of boom sprayers regarding their conservation status in order to identify the problems that interfere with quality sprayings. Sixty-three agricultural sprayers from rural properties were evaluated in the micro-region of Pato Branco, PR. Less than half of applicators (42.9%) performed some type of training and 58.7% of the operators had knowledge about the working pressure indicated by the spray tip manufacturer, but 24.3% of them were working with the pressure out of the recommended or with a damaged manometer. The manometer was present and operative in only 71.4% of the sprayers. Only 54% of the collected flows were in accordance with that informed by the operator. Most of the interviewed producers still do not have adequate criteria for choosing spray tips nor frequency of their replacement.